CXCL12 Promotes Stem Cell Recruitment and Uterine Repair after Injury in Asherman’s Syndrome - Sahin Ersoy, Gulcin (Mol Ther Methods Clin Dev, 2017)
Asherman’s syndrome is an acquired condition of uterine fibrosis and adhesions in response to injury that adversely affects fertility and pregnancy. We have previously demonstrated that bone marrow-derived mesenchymal stem cells (BMDSCs) contribute to uterine repair after injury and that stem cells supplementation improves fertility. Here, we demonstrate that CXCL12 is the chemokine that mediates stem cell engraftment and functional improvement using a murine model of Asherman’s syndrome. After uterine injury, we demonstrate that CXCL12 augmentation increased BMDSC engraftment and that the CXCL12 receptor (CXCR4) antagonist, ADM3100, blocked stem cell recruitment. CXCL12 reduced, whereas ADM3100 increased fibrosis. CXCL12 treatment led to improved fertility and litter size, whereas ADM3100 treatment reduced fertility and litter size. ADM3100 prevented optimal spontaneous uterine repair mediated by endogenous CXCL12 production, reducing pregnancies after injury in the absence of supplemental CXCL12 administration; however, ADM3100 treatment could be partially rescued by CXCL12 augmentation. CXCL12 or other CXCR4 receptor agonists may be useful in the treatment of infertility or adverse pregnancy outcomes in Asherman’s syndrome and other related uterine disorders.